Analisis Kesalahan Siswa dalam Menyelesaikan Soal Eksponen Menggunakan Prosedur Newman - Susanti, Wiwit; Roza, Yenita; Maimunah, Maimunah (Jurnal Gantang, 2025)
Exponents constitute a fundamental concept essential for understanding advanced mathematical topics such as logarithms, geometric sequences, and compound interest. However, many students continue to experience difficulties in solving exponent-related problems. This qualitative descriptive study aims to analyze the types of errors made by tenth-grade students when solving exponent problems using Newman’s procedure and to investigate the factors contributing to these errors. The participants were 23 students from Madrasah Aliyah Negeri (MAN) Insan Cendekia Siak in the 2024/2025 academic year. Data were collected through written tests and interviews, then analyzed by organizing and categorizing students’ errors according to Newman’s five stages. The results show that 12% of students committed reading errors due to inaccuracies in interpreting the questions, while no comprehension errors were identified. Transformation errors were the most common (49%), primarily due to students’ difficulties in constructing appropriate mathematical models. Process skill errors accounted for 21%, primarily due to computational mistakes, and encoding errors represented 18%, arising from students’ inability to use the provided information effectively. These findings deepen the understanding of students’ patterns of error in exponent problems and imply the need for more targeted instructional strategies, especially those that strengthen mathematical modeling and procedural accuracy.